2019
DOI: 10.20527/jvk.v34i1.6443
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pembelajaran Saintifik Pada Pembelajaran Fisika Sma Topik Materi Elastisitas Dan Hukum Hooke

Abstract: Abstract. The purpose of this study was to describe the results of the implementation of scientific learning on the topic of elasticity and Hooke's law relating to: (1) students 'science process skills and (2) students' learning outcomes completeness. This study was a pre-experimental study using a one-shot case study design. The research subjects were the 24 students of class XI MIA-4 in one of the senior high schools in Palangka Raya City. Based on the results of data analysis, the completeness of student le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Salah satu poin penting dari temuan penelitian ini adalah bahwa praktik pembelajaran dengan pendekatan ilmiah memberikan dampak positif kepada Purwaningtyas, H., Hartanto, T.J., & Sinulingga, P./Vidya Karya 35 (1) 2020 11-20 peserta didik berkaitan dengan keterampilan proses sains. Hasil ini menguatkan sejumlah studi sebelumnya (Putri, Sinulingga & Hartanto, 2019;Chairam, Klahan, & Coll, 2015;Chabalengula, Mumba & Mbewe, 2012;Sevli, Turkaslan, & Yigitarslan, 2013). Peserta didik terus dilatih selama pembelajaran di kelas untuk merumuskan hipotesis, memilih dan merangkai alat percobaan, melaksanakan percobaan dalam rangka mengumpulkan data, menganalisis data yang diperoleh, serta menyimpulkan hasilnya berbasis data yang diperoleh.…”
Section: Gambar 3 Ketuntasan Hasil Belajar Peserta Didikunclassified
“…Salah satu poin penting dari temuan penelitian ini adalah bahwa praktik pembelajaran dengan pendekatan ilmiah memberikan dampak positif kepada Purwaningtyas, H., Hartanto, T.J., & Sinulingga, P./Vidya Karya 35 (1) 2020 11-20 peserta didik berkaitan dengan keterampilan proses sains. Hasil ini menguatkan sejumlah studi sebelumnya (Putri, Sinulingga & Hartanto, 2019;Chairam, Klahan, & Coll, 2015;Chabalengula, Mumba & Mbewe, 2012;Sevli, Turkaslan, & Yigitarslan, 2013). Peserta didik terus dilatih selama pembelajaran di kelas untuk merumuskan hipotesis, memilih dan merangkai alat percobaan, melaksanakan percobaan dalam rangka mengumpulkan data, menganalisis data yang diperoleh, serta menyimpulkan hasilnya berbasis data yang diperoleh.…”
Section: Gambar 3 Ketuntasan Hasil Belajar Peserta Didikunclassified
“…Implementing Curriculum 2013 in the learning process requires a scientific approach that allows students to obtain concepts through activities and phenomena to improve student learning outcomes (Setyawan et al, 2017). Several studies have shown that the application of scientific learning in the classroom has a positive impact on the completeness of cognitive learning outcomes (Putri et al, 2019;Murtini, 2018). However, applying the 2013 curriculum with a scientific approach has not been maximized (Amin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%